Accounting of passenger transportation in the conditions of automated passenger flow management - Zadorozhnyi, Zenovii-Mykhailo; Kornyat, Iryna (Herald of Economics, 2022)
Introduction. Further development of urban formations requires optimization of passenger traffic management in the public transport network. Ensuring the efficiency of traffic flow management involves improving accounting with the use of innovative NFC- validation and GPS-navigation systems simultaneously for all participants in passenger traffic. The purpose of the article. The main aim is to provide proposals for improving the cost and revenue accounting of carriers and issuers of electronic tickets for NFC validators in terms of information interaction of all participants in passenger traffic to ensure the effectiveness of automated passenger traffic management in the smart city.Methods. General scientific and empirical methods of cognition of processes and phenomena are used to reveal the purpose of the article.Results. A method of using information from the automated passenger traffic management system using NFC-validation and GPS-navigation technologies on the number of transported passengers to identify costs and revenues of public transport participants has been developed. The procedure for determining the cost of transportation of one passenger on the basis of additive accumulation of costs of carriers and issuers of electronic tickets has been improved. It is proposed to recognize the funds received from the sale of electronic tickets as targeted revenue (targeted funding). The method of accounting for revenues of issuers of electronic tickets and carriers has been improved. Implementation of the proposed method of parallel recognition and accounting of revenues and costs simultaneously for issuers of electronic documents and passenger carriers provides optimization of management in all market participants of passenger transport, which will lead to optimization: transport routes, service quality, reliability of accounting, socio-economic processes making managerial decisions, etc.Perspectives. Further research will be aimed at improving the methodology of control over the functioning of passenger carriers and the transport network of public entities in the implementation of an automated passenger traffic management system.